(untitled) (KYAMC Journal, 2017)
During Ramadan, Muslims fast from dawn to dusk for one lunar month. Although a majority of Muslim patients with type 2 diabetes fast during the month of Ramadan, there are no accepted guidelines for its management during this period. The few studies on this subject suggest that there are important alterations in energy intake and physical activity, and that most patients change their pattern of drug intake. The objectives of this article is to assist in the task of advising diabetic patients who fast and provide them with guidelines regarding proper management of their diabetes during Ramadan. KYAMC Journal Vol. 6, No.-2, Jan 2016, Page 649-652